Wydobycie węgla brunatnego na Ziemi Lubuskiej = The brown coal mining in the Lubuski Region - Kołodziejczyk, Urszula; Asani, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Lubuski Region is part of the Miocene coal-bearing province, which builds the upper stages of the Fore-Sudetic monocline. There are numerous brown coal deposits here ? bedded (undisturbed) or glacitectonically deformed (during the Pleistocene glaciations). In the Polish part of the Middle Odra Region, are the following deposits: Babina, Cybinka, Gubin, Brody, Mosty, Żary, Zielona Góra and Sieniawa, where altogether approx. 2.2 billion Mg of the resources have been documented.
Keywords: węgiel brunatny - eksploatacja; Ziemia Lubuska; brown coal; mining; The Lubuski Region